Editorial Commentary: Arthroscopic lower trapezius tendon transfer using achilles tendon allograft for isolated, irreparable infraspinatus musculotendinous tear is durable - Jaber, Ayham; Hawryluk, Christopher J.; Millett, Peter J. (Arthroscopy, 2025)
Tendon transfers represent a reconstructive option for irreparable rotator cuff tears and certain neurologic deficiencies. Arthroscopically assisted lower trapezius tendon (aLTT) transfer using Achilles tendon allograft is effective in restoring external rotation and relieving excessive loading on the teres minor. It has shown good results in patients with brachial plexus injuries and posterosuperior irreparable rotator cuff tears. Isolated infraspinatus musculotendinous tears present distinct characteristics compared with other rotator cuff tears, as these lesions cause rapid atrophy and significant fatty infiltration within the muscle, making direct surgical repair less feasible. Tears of the infraspinatus tendon usually are associated with other rotator cuff injuries but can be isolated injuries, and tear at the musculotendinous junction of the tendon is a less common. Existing literature predominantly focuses on nerve-related causes of infraspinatus deficiency, such as in Parsonage-Turner syndrome or suprascapular nerve entrapment, which may be secondary to ganglion cysts along the nerve's path as well as other space-occupying lesions like tumors or vascular malformations. Infraspinatus muscle tendon injuries also can result from steroid injections and lead to severe pain and weakness during external rotation. Primary repair of the tear is a first choice if nonsurgical treatment is unsuccessful and if tear morphology and fatty infiltration allow. However, repair has a low success rate because of the aforementioned features. For older, low-demand patients, subacromial debridement or the use of a biodegradable subacromial balloon spacer can provide pain relief and functional improvement. In younger, more active patients, aLTT transfer using Achilles tendon allograft, although technically demanding and uncommonly performed, is a durable solution for this pathology when glenohumeral osteoarthritis and joint arthropathy are absent, offering sustained benefits at midterm follow-up. Other alternatives include latissimus dorsi tendon transfer, lower trapezius transfer (which may be biomechanically superior to latissimus dorsi tendon transfer), and reverse total shoulder arthroplasty. We thus consider aLTT to be a strong option for the right patient, performed by a skilled surgeon who can execute the procedure properly.
Online verfügbar: 23. März 2025, Artikelversion: 31. Juli 2025
Gesehen am 09.01.2026